Working smarter and greener: Collaborative knowledge sharing in virtual global project teams. Issue 1 (February 2017) - Olaisen, Johan; Revang, Oivind
Highlights: Competence-based trust ties are essential for knowledge sharing of high-quality knowledge in virtual project teams. We can develop trust and social interaction online without offline face-to-face meetings. We can establish and share actionable, contextual and intrinsic knowledge online. We can reduce traveling with 50–70% in virtual project teams using social, technological platforms for knowledge sharing. Managers and employees are more satisfied and deliver better solutions when they are working smarter and greener online. Abstract: The purpose of this study is to explore how to facilitate the sharing of high-quality knowledge in a virtual global project team context. The most obvious finding from this study is that we can develop social interaction building up trust and share knowledge through online technology platforms without offline social interaction. The design and methodology are case studies of four Scandinavian virtual global project teams with a total of 42 team members. The survey is a longitude study in 2014-16 based upon 168 individual reports and 16 in-depth top leader interviews. Working smarter means using technology platforms for developing trust and knowledge collaboration to deliver business solutions and innovations. Working smarter mean to work in a global project team where the collaboration results develop the team into a high-performance team. Working more intelligent is sharing knowledge to improve innovation and collective and individual competence growth. Understanding that investment in top technology solutions are inexpensive compared to the results delivered by professional human resources. Working greener means to let the team members be aware of green solutions and innovations. Working greener means to travel less using the possibilities given by social technology platforms. The four teams reduced the number of trips by 50–70%. The result is less airline pollution, less stress, and more professional work.